Nutritional characteristics and strategies to enhance utilization of tropical feeds for low resource livestock producers - Nsahlai, I.V.; Sileshi, Z.; Bediye, S.; Umunna, N.N. (Ethiopian Society of Animal Production, 1996)
Livestock under holdings of low-resource producers in the tropics are faced with a variety of feeds that are qualitatively and quantitatively deficient in available nutrients. Emerging practices of hay-making and inter-cropping of cereal with legumes have improved feed quality, but the lack of appropriate post-harvest technologies have introduced further variation in quality. This review contends and shows that roughages can be put into groups within which members are more like one another than they are like members of other groups with respect to animal responses when these are fed with or without supplementation with forage legumes (FL). The review also acknowledges the deficiency of chemical properties alone in the identification and selection of potential forage supplements and suggests an integrated approach incorporating agronomic characteristics and biological indices of feed quality. Results from various Reports were integrated to identify indices that could be used to delineate forage legumes are good sources of rumen degradable N, but only a few (e.g., Desmodium intortum, Chamaecytisus palmensis and Leucaena leucocephala) are potential sources of escape protein. Because there is no clear reconciliation between Reports on important attributes of forage legumes, it was only possible in a few instances to synthesise Reports in the context of FL factors that influence responses. Despite the paucity of relevant data, the level of supplementation with FL that maximizes roughage intake is quite different from that which optimizes digestibility or productivity. The picture is made more complex by the possibility of interaction between supplementation and roughage quality on animal responses. This review attempts to identify hiatus in nutrition research which according to the authors would yield the most benefit.